2016
DOI: 10.1038/srep21244
|View full text |Cite
|
Sign up to set email alerts
|

Hyporesponsiveness to the anti-inflammatory action of interleukin-10 in type 2 diabetes

Abstract: Chronic low-grade inflammation contributes to the pathology and complications of type 2 diabetes (T2D). Interleukin-10 (IL10), an anti-inflammatory cytokine, is suggested to play a protective role in T2D. However, the impact of T2D on IL10 function has not been previously assessed. We examined the ability of IL10 to inhibit inflammation in human T2D immune cells and explored underlying mechanisms using macrophage models. IL10 was less effective at inhibiting tumour necrosis factor (TNF)-α secretion in T2D whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
114
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(120 citation statements)
references
References 39 publications
(59 reference statements)
5
114
0
1
Order By: Relevance
“…The mode of action of IL-10 in preventing diabetes was mostly linked to its properties as an anti-inflammatory cytokine [14,15,16,23,24]. However, the decrease of blood glucose in this research was not likely related to antiinflammatory activity of IL-10, since no inflammation occurred in any of the experimental groups.…”
Section: Effect Of S Grandiflora Seed Decoction On Relative Amount Omentioning
confidence: 64%
See 2 more Smart Citations
“…The mode of action of IL-10 in preventing diabetes was mostly linked to its properties as an anti-inflammatory cytokine [14,15,16,23,24]. However, the decrease of blood glucose in this research was not likely related to antiinflammatory activity of IL-10, since no inflammation occurred in any of the experimental groups.…”
Section: Effect Of S Grandiflora Seed Decoction On Relative Amount Omentioning
confidence: 64%
“…[23][24] In particular, Goudy et al 14 and Goudy et al 15 found that IL-10 could be used to prevent type 1 diabetes in mice. The role of IL-10 in protection from type 2 diabetes was reported by Bary et al 16 The data were analized by Analysis of Variance (ANOVA) followed by Duncan's Multiple Range Test (DMRT).…”
Section: Effect Of S Grandiflora Seed Decoction On Relative Amount Omentioning
confidence: 99%
See 1 more Smart Citation
“…IL-10 is produced by macrophages 27,28 . In this study, the increasing 150. of IL-10 may happen not only due to macrophage related Th-2 activation but also due 151. to insulin attenuated anti-inflammation regulatory [29][30][31][32] .…”
mentioning
confidence: 92%
“…IL-10 a major anti-inflammatory cytokines plays important role in metabolic disorder 143. such diabetes due its affect to insulin sensitivity 29 . IL-10 is produced by macrophages 27,28 .…”
mentioning
confidence: 99%